2020
DOI: 10.3390/foods9121829
|View full text |Cite
|
Sign up to set email alerts
|

Opinions on Insect Consumption in Hungary

Abstract: The aim of the study was to assess knowledge and opinion in the Hungarian population about the consumption of insect-based food. The questionnaire was filled in by 414 respondents. Their knowledge of edible insect consumption in different countries was average (score 4) or above on a scale of 1 (totally disagree) to 7 (totally agree). Their willingness to consume insect-based food was low, usually below average. Significantly higher scores were attained by men than women, by respondents with a university degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
3
22
1
Order By: Relevance
“…Results regarding the influence of place of residence on consumers' acceptance of insects as food are similar to the results concerning education, though place of residence was less often examined ( 42 , 65 , 67 , 71 , 87 , 93 , 99 , 105 , 116 ). The place of residence was surveyed with various methods that can be broadly divided into two categories: [1] number of residents and [2] designation of residence (e.g., urban vs. not urban, city vs. rural).…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…Results regarding the influence of place of residence on consumers' acceptance of insects as food are similar to the results concerning education, though place of residence was less often examined ( 42 , 65 , 67 , 71 , 87 , 93 , 99 , 105 , 116 ). The place of residence was surveyed with various methods that can be broadly divided into two categories: [1] number of residents and [2] designation of residence (e.g., urban vs. not urban, city vs. rural).…”
Section: Resultssupporting
confidence: 63%
“…If the place of residence had an effect, which was the case in 44.4% of the studies, people living in an urban area or in areas with a high number of residents were found to be more receptive to edible insects ( 65 , 71 , 99 , 116 ). In contrast, the majority of studies (55.6%) found that the place of residence had an insignificant effect ( 42 , 67 , 87 , 93 , 105 ).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations